Growth and skeletal maturation in children with phenylketonuria - Schaefer, Franz; Burgard, P.; Batzler, U.; Rupp, André; Schmidt, Hildgund; Gilli, G.; Bickel, Horst; Bremer, Hans J. (Acta paediatrica, 1994)
Schaefer F, Burgard P, Batzler U, Rupp A, Schmidt H, Gilli G, Bickel H, Bremer HJ. Growth and skeletal maturation in phenylketonuria. Acta Paediatr 1994;83:534-41. Stockholm. ISSN 0803-5253 Growth and skeletal maturation was evaluated in 82 children participating in the German Colkdborative Study of Children Treated for Phenylketonuria (PKU). Height, weight, head circumference and bone age were recorded at regular intervals for the first 6 years of life. The mean SD score (SDS) for height was not significantly different from zero at study entry, but decreased mainly during the second year of life to a nadir of -0.78 in boys and -0.54 in girls at 2.5 years. During the subsequent years, a significant trend towards a regain of height SDS was noted in both sexes. Weight-for-height SDS was close to zero in both sexes, with a significant continuous increasing trend throughout the observation period. Head circumference SDS decreased in boys during the first year of life from -0.28 to -0.68, whereas girls showed only a minor change. During the further follow-up period, head circumference SDS remained at approximately -0.3 in boys and 0.0 in girls. While the mean verbal and performance IQ of the total study population at 5 and 6 years of age did not differ from a group of 212 healthy non-PKU children, patients with a head circumference SDS less than the population median at 2 years of age exhibited poorer cognitative abilities at school age than those patients with a relative head size greater than the population median. The children with a head circumference less than the median at 2 years had smaller head sizes already at birth; in addition, the change in relative head size during the first 2 years was correlated significantly with cognitive abilities at school age in boys. Mean bone age was identical to chronological age at each time point of observation. The rate of maturation was one year of bone age per year of chronological age. No correlation between phenylalanine intake or phenylalanine concentrations and the rates of body or head growth or skeletal maturation could be established. We conclude that despite adequate weight gain, moderate growth retardation occurred during the first 2 years of life in this group of children treated for PKU. Growth was more compromised in boys than in girls and tended to be compensated during later follow-up. Early infantile head circumference and growth appear to be predictors of cognitive development.